2003
DOI: 10.1530/eje.0.1480055
|View full text |Cite
|
Sign up to set email alerts
|

Do reproductive hormones modify insulin sensitivity and metabolism in older men? A randomized, placebo-controlled clinical trial of recombinant human chorionic gonadotropin

Abstract: Objective: In order to assess the hormonal determinants of insulin sensitivity and related components of the metabolic syndrome, we evaluated the effect of subcutaneous recombinant human chorionic gonadotropin (r-hCG; Ovidrel) on insulin sensitivity, vascular reactivity, leptin, insulin-like growth factor-I (IGF-I) and lipids in ambulant, community dwelling men .60 years of age with serum testosterone # 15 nmol/l on two occasions. Design: Forty eligible men were randomized to receive 250 mg (5000 IU) r-hCG sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 95 publications
3
40
0
1
Order By: Relevance
“…In accordance with our findings, four placebo-controlled studies of testosterone therapy in aging men found no effect on insulin sensitivity using surrogate markers of insulin resistance such as the minimal model (Basu et al 2007;Nair et al 2006) and HOMA-IR (Svartberg et al 2008;Emmelot-Vonk et al 2008). Correspondingly, a placebo-controlled, double-blinded study of aging men treated with HCG therapy to increase endogenous testosterone serum levels showed no increase in insulin sensitivity measured by the euglycemic hyperinsulinemic clamp despite an increase in LBM (Liu et al 2003). On the other hand, two placebo-controlled, double-blinded studies have reported an increase in insulin sensitivity during testosterone therapy assessed by the euglycemic hyperinsulinemic clamp in obese middle-aged men, in whom no predefined cutoff level for testosterone was used (Marin et al 1992;Marin et al 1993).…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with our findings, four placebo-controlled studies of testosterone therapy in aging men found no effect on insulin sensitivity using surrogate markers of insulin resistance such as the minimal model (Basu et al 2007;Nair et al 2006) and HOMA-IR (Svartberg et al 2008;Emmelot-Vonk et al 2008). Correspondingly, a placebo-controlled, double-blinded study of aging men treated with HCG therapy to increase endogenous testosterone serum levels showed no increase in insulin sensitivity measured by the euglycemic hyperinsulinemic clamp despite an increase in LBM (Liu et al 2003). On the other hand, two placebo-controlled, double-blinded studies have reported an increase in insulin sensitivity during testosterone therapy assessed by the euglycemic hyperinsulinemic clamp in obese middle-aged men, in whom no predefined cutoff level for testosterone was used (Marin et al 1992;Marin et al 1993).…”
Section: Discussionsupporting
confidence: 90%
“…74,75 Three randomized controlled trials (RCTs) in older men with low-normal serum testosterone have examined the effect of physiological androgen replacement on vascular reactivity. 42,76,77 No change in FMD was seen with 3 months of DHT 42 or hCG 76 or with 12 months of transdermal testosterone. 77 FMD was increased with short-term physiological and acute supraphysiological testosterone treatments in middleaged men with underlying coronary artery disease.…”
Section: Relationship Of Endogenous Testosterone To Markers Of Cardiomentioning
confidence: 91%
“…55 In ageing men, hCG administered for 3 months did not affect insulin sensitivity (as measured by euglycaemic clamp). 76 It is unclear as to whether changes in serum testosterone mediate insulin sensitivity independent of their effect on FM (specifically visceral fat). Comparison of data sets is difficult as those middle-aged men showing improved insulin sensitivity had higher FM and greater waist circumference at baseline 52 Body composition, metabolic syndrome and testosterone in ageing men CA Allan et al than the ageing men treated with hCG.…”
Section: Relationship Of Endogenous Testosterone To Markers Of Cardiomentioning
confidence: 99%
See 1 more Smart Citation
“…A bidirectional relation is possible where obesity and hyperinsulinemia induce a decrease in T levels, which in turn have a negative effect on body composition and insulin levels. Conversely, as supported by a study by Liu et al [97] on non diabetic obese men, TRT has a positive effect of on insulin sensitivity. TRT also improved glycemic control in hypogonadal men with T2D [98].…”
Section: Cardiovascular Diseasementioning
confidence: 80%